Employing arynes in transition-metal-free monoarylation of aromatic tertiary amines - Bhojgude, Sachin Suresh; Kaicharla, Trinadh; Biju, Akkattu T. (Organic Letters, 2013)
The highly monoselective N-arylation of aromatic tertiary amines using a transition-metal-free approach using arynes has been developed. The reaction afforded functionalized diaryl amines in moderate to excellent yield. High levels of functional group compatibility especially with halogen containing substrates, dyes and donor-acceptor systems, and high yields of products are the notable features of the present reaction.